2008
DOI: 10.1007/s11205-008-9359-8
|View full text |Cite
|
Sign up to set email alerts
|

Life Domain Satisfaction: A Portugal–France Comparison

Abstract: Satisfaction with life, Domains of life, Portugal, France,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
4
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 31 publications
2
4
0
Order By: Relevance
“…Current findings are consistent with what has been previously observed about quality of life (Arun & Çevik, 2011) and life domain satisfaction in Portugal (Paiva et al, 2009). For example, Paiva et al (2009) point out that many elderly persons in Portugal were financially very deprived without resources to consecrate to leisure, and tend to experience loneliness. However, another possible type of explanation for age trends in loneliness, methodological artefacts, should be mentioned.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Current findings are consistent with what has been previously observed about quality of life (Arun & Çevik, 2011) and life domain satisfaction in Portugal (Paiva et al, 2009). For example, Paiva et al (2009) point out that many elderly persons in Portugal were financially very deprived without resources to consecrate to leisure, and tend to experience loneliness. However, another possible type of explanation for age trends in loneliness, methodological artefacts, should be mentioned.…”
Section: Discussionsupporting
confidence: 93%
“…Our expectation was that the effect of age on the loneliness in the present study supports the first model. This is because, as convincingly illustrated by Paiva et al (2009), given the very bad conditions in which some old people live in Portugal, multiple life domains satisfaction decreases, particularly financial resources and social relationships, as well as a decrease in overall satisfaction as function of age were found. Thus our expectation was that we would find a growth in loneliness in old age.…”
mentioning
confidence: 87%
“…In particular, previous research showed that specific life satisfaction domains and life satisfaction are linked (Neto & Fonseca, 2018;Ruiz Paiva et al, 2009). The results of the current study confirm this observation as life satisfaction and love life satisfaction were significantly correlated (r = .42).…”
Section: Discussionsupporting
confidence: 89%
“…The SWFLS scores correlated strongly with life satisfaction and family support, demonstrating the convergent validity of the scale. Past research has also shown strong relationships between life satisfaction and domains of life satisfaction (Ruiz et al, 2009). Higher levels of satisfaction with family relationships were associated with higher overall life satisfaction (Schimmack et al, 2002;Schnettler et al, 2017).…”
Section: Discussionmentioning
confidence: 83%